A Circular Disc Microstrip Antenna with Dual Notch Band for GSM/Bluetooth and Extended UWB Applications - Kumar, Sanjeev; Kumar, Ravi; Kumar Vishwakarma, Rajesh (International Journal of Engineering and Technology, 2018)
A microstrip antenna with a circular disc design and modified ground is proposed in this paper. Circular shapes of different size have been slotted out from the radiating patch for achieving extended ultra wideband (UWB) with GSM/Bluetooth bands with maximum bandwidth of 17.7 GHz (0.88-18.6 GHz). Further, characteristic of dual notch band is achieved, when a combination of T and L-shaped slots are etched into the circular disc and ground plane respectively. Change in length of slots is controlling the notch band characteristics. The proposed antenna has rejection bandwidth of 1.3-2.2 GHz (LTE band), 3.2-3.9 GHz (WiMAX band) and 5.2-6.1 GHz (WLAN band) respectively. It covers the frequency range of 0.88-18.5 GHz with the VSWR of less than 2. Also, an equivalent parallel resonant circuit has been demonstrated for band notched frequencies of the designed antenna. The gain achieved by the proposed antenna is 6.27 dBi. This antenna has been designed, investigated and fabricated for GSM, Bluetooth, UWB, X and Ku band applications. The stable gain including H & E-plane radiation pattern with good directivity and omnidirectional behavior is achieved by the proposed antenna. Measured bandwidths are 0.5 GHz, 0.8 GHz, 1.1 GHz and 11.7 GHz respectively.